Clinical Characteristics and Histopathological Patterns of Hodgkin Lymphoma and Treatment Outcomes at a Tertiary Cancer Center in Ethiopia. (2021) - Adam, Makka; Bekueretsion, Yonas; Abubeker, Abdulaziz; Tadesse, Fisihatsion; Kwiecinska, Anna; Howe, Rawleigh; Petros, Beyene; Jerkeman, Mats; Gebremedhin, Amha
Abstract : PURPOSE: In developing countries, Hodgkin lymphoma (HL) affects the young population. In Ethiopia, nearly 70% of the population are < 35 years of age. Therefore, this study aimed to elucidate the age distribution, histopathologic patterns, clinical characteristics and treatment outcomes of HL in Ethiopia. MATERIALS AND METHODS: Data from clinical records of 133 consecutive patients with HL between 2014 and 2019 were reviewed and collected. Formalin-fixed paraffin-embedded tissue blocks of HL cases were collected and used for subtype classification. RESULTS: A total of 68.4% (91) of the patients were male; male-to-female ratio was 2.2:1. The median age was 22 years. The age distribution was 57.1% (76), 30.8% (41), and 2.3% (3) for the age groups (10-29), (30-59), and (60-69) years, respectively. Thirteen percent (12) were associated with HIV. The majority of the cases, 50.4% (67), were of the mixed-cellularity (MCCHL) subtypes and 30% (40) nodular-sclerosis (NSCCHL). Most HIV-associated cases (60%, 6) were of the MCHL subtype. The 4-year overall survival (OS) was 83.1%. The 4-year OS of early-stage patients was 100% and advanced-stage patients with low-risk (International Prognostic Score [IPS] ⩽ 2) and high-risk (IPS ≥ 3) were 94.1% and 62.9%, respectively. All patients who received combined-therapy survived, whereas those who received doxorubicin, bleomycin, vinblastine, and dacarbazine only showed a 4-year OS rate of 77.9%. CONCLUSION: HL affects the youngest and most productive population in Ethiopia. The treatment outcome is favorable in both HIV-associated and non–HIV-associated HL. However, the study population was likely a highly selected group as the majority of the Ethiopian population do not have access to specialized care.